Exploring the Association Between of Food and Nutrition Literacy to Food Insecurity and Nutritional Status: A Scoping Review - Ulfatul Karomah; Fani Cahya Wahyuni (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Abstract: According to FAO data, by 2023, around 152 million people experienced food insecurity, and 733 million were undernourished. It is estimated that nearly 600 million people will still face hunger by 2030. This review aims to explore the association between nutrition and food literacy with food security and nutritional status. A scoping review was conducted using literature searches from Google Scholar, PubMed, and ScienceDirect. The inclusion criteria involved general population groups, with nutrition or food literacy as the exposure and food security or nutritional status as the outcome. A total of 293 studies were identified, and 11 met the inclusion criteria. Four studies demonstrated a direct association between nutrition or food literacy and food security, indicating that poor literacy was associated with higher food insecurity, especially among adolescents and adults. Among the eight studies examining the association with nutritional status, six found no significant association, while two showed a positive association. Results varied depending on the participant characteristics, study design, and measurement instruments. Several factors were identified as predictors of adequate food and nutrition literacy, such as urban residence, higher education level, working participants, number of children, having received nutrition education, and the presence of chronic diseases. Food and nutrition literacy is directly linked to food security and indirectly to nutritional status through improved dietary behaviors. This review supports future research and programs to strengthen food and nutrition literacy to enhance food security and nutritional outcomes.